2014
DOI: 10.1002/jmri.24645
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of arterial spin labeling perfusion MRI to pharmacologically induced perfusion changes in rat kidneys

Abstract: Purpose To investigate whether arterial spin labeling (ASL) MRI is sensitive to changes by pharmacologically induced vasodilation and vasoconstriction in rat kidneys. Materials and Methods Changes in renal cortical blood flow in seven rats were induced by Adenosine infusion (vasodilation) and L-NAME injection (vasoconstriction). All imaging studies were performed on a 3T scanner using a FAIR-TrueFISP sequence for the ASL implementation. The acquisition length for each ASL scan was 6 minutes. Cortical perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…Using ASL for the quantification of transient changes of renal cortical perfusion after the application of diclofenac was feasible in our study. This is in line with previous pharmacological studies, using ASL to monitor changes of renal perfusion after pharmacologically induced vasodilatation and vasoconstriction in rats [43] and after application of furosemide in healthy human participants. [44] Furthermore, we could show an excellent inter-reader reproducibility when two independent readers analysed ASL maps, underlining the robust aspect of the method used for data analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Using ASL for the quantification of transient changes of renal cortical perfusion after the application of diclofenac was feasible in our study. This is in line with previous pharmacological studies, using ASL to monitor changes of renal perfusion after pharmacologically induced vasodilatation and vasoconstriction in rats [43] and after application of furosemide in healthy human participants. [44] Furthermore, we could show an excellent inter-reader reproducibility when two independent readers analysed ASL maps, underlining the robust aspect of the method used for data analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Otherwise, if quantitative values are reported reference ranges obtained from healthy volunteers at each imaging centre may be necessary [32]. Previous studies have shown the sensitivity of ASL to map dynamic changes in renal perfusion during administration of adenosine [33], protein load [34] and furosemide [35]. GTN is known to be a potent venodilator with the acute effect mainly being a reduction of systolic blood pressure due to an increase in arterial compliance and a decrease in venous return resulting in reflex tachycardia [36].…”
Section: Discussionmentioning
confidence: 99%
“…ASL was able to monitor perfusion alterations induced by administration of vasoactive drugs [37], protein loading challenges [30] and furosemide [38]. …”
Section: Renal Asl Mri In Healthy Volunteersmentioning
confidence: 99%